(untitled) (World Bulletin of Social Sciences, 2022)
In this article, data are given on the role of photosynthetic activity of plants, the need for soybean cultivation in Uzbekistan, the importance of soybean culture, conditions and methods of experiments, agro-technics of the experiment, the development of soybean leaves, the formation of the leaf area of one plant and the leaf area per hectare. The optimal norms of phosphate fertilizers are determined, and used references are listed.